2018
DOI: 10.3389/fphar.2018.00225
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Therapy for Drug Repositioning to Reduce the Risk of Prostate Cancer Mortality in Patients With Hyperlipidemia

Abstract: Prostate cancer (PCa) is one of the most commonly diagnosed cancers in the western world, and the mortality rate from PCa in Asia has been increasing recently. Statins are potent inhibitors of 3-hydroxy-3-methyl glutaryl coenzyme A (HMG-CoA) reductase and are commonly used for treating hyperlipidemia, with beneficial effects for cardiovascular disease and they also exhibit anti-cancer activity. However, the protective effects of statins against PCa are controversial. In this study, we investigated the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…Among these drugs, statins are widely used to retard the atherosclerosis in patients with hyperlipidemia (Macan et al, 2015). In fact, these drugs have also been reported to present anti-inflammatory, anticancer, antioxidant and immunomodulatory effects (Chen et al, 2018;Rizvi et al, 2019). Experiments in vivo and in vitro have shown that statins protect organism damage from oxidative stress by eliminating superoxide anion and hydroxyl radicals (Murakami et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Among these drugs, statins are widely used to retard the atherosclerosis in patients with hyperlipidemia (Macan et al, 2015). In fact, these drugs have also been reported to present anti-inflammatory, anticancer, antioxidant and immunomodulatory effects (Chen et al, 2018;Rizvi et al, 2019). Experiments in vivo and in vitro have shown that statins protect organism damage from oxidative stress by eliminating superoxide anion and hydroxyl radicals (Murakami et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have shown that statins decrease the incidence of advanced PCa, including radioresistant PCa ( Hindler et al, 2006 ; Pisanti et al, 2014 ). In addition, our recent studies using a population-based cohort demonstrated that statin prescriptions remarkably reduced the risk of death in PCa patients undergoing radiotherapy ( Sun et al, 2015 ; Chen et al, 2018 ). Although the radiosensitizing properties of statins and their potential effects in inhibiting PCa have been reported, the molecular mechanism underlying this outcome has not been clearly explored ( Alfaqih et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Repurposed medications can likewise minimize a great percentage of the early expense and time expected to offer a medication for sale to the public, thereby cutting the time between the research bench work and treatment at bedside (Papapetropoulos & Szabo, ). Simvastatin treatment experienced medication repositioning to diminish the danger of prostate malignant growth mortality in patients with hyperlipidemia (Chen et al, ). Colesevelam as a monotherapy of essential hyperlipidemia could be endorsed to improve diabetes control (Fonseca, Rosenstock, Wang, Truitt, & Jones, ; Sekhri & Saha, ).…”
Section: Introductionmentioning
confidence: 99%